Principles of Antibiotic Therapy in the Treatment of Children with Bacterial Infections of the Respiratory Tract in Outpatient Settings - O.Ye. Abaturov; T.P. Borysovа (Zaslavsky O.Yu., 2016)
The paper presents the data on the selection and rational use of antibiotics in the treatment of acute respiratory infections in children caused by a variety of etiologically significant microorganisms.